T-cell exhaustion due to BiTE therapy in multiple myeloma: mitigating infectious risks through treatment-free intervals - Dean, Erin A. (Frontiers in Immunology, 2026)
Multiple Myeloma (MM), a highly treatable but thus far incurable hematologic malignancy, has required continuous monitoring and treatment throughout a patient’s lifetime. Newer classes of therapies, such as chimeric antigen receptor (CAR) T-cell therapy which constitutes of a one-time infusion, have challenged the continuous treatment paradigm. Compared to previously known standard therapies, CAR T-cell therapy along with bispecific T-cell engager (BiTE) therapy have been observed to induce deeper responses that tend to be durable in responders. However, the degree of immunosuppression and infection noted especially with BiTE therapies, currently approved for ongoing administration until progression of disease, has given rise to the idea of incorporating treatment-free intervals. This review describes T-cell exhaustion as a driver for immunosuppression and infection in patients with MM receiving BiTE therapy and discusses potential ways to overcome it to improve management of patients.